PENGARUH SOLVABILITAS, PROFITABILITAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP RETURN SAHAM - Wildan Army Abdillah; Muhammad Iqbal Nurfauzan; Rengga Madya Pranata (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2021)
This study aims to examine and analyze the effect of Solvency, Profitability, and managerial ownership on Stock Returns in non-BUMN basic and chemical industrial companies listed on the Indonesia Stock Exchange during the 2010-2019 period. The population in this study are basic and chemical industrial companies listed on the Indonesia Stock Exchange. A sample of 41 companies was taken using purposive sampling technique. Multiple regression analysis was used to test the hypothesis with the help of Eviews software version 9. The results showed that profitability partially had a positive and significant effect. Meanwhile, solvency and managerial ownership have no effect on stock returns of non-BUMN basic and chemical industrial companies listed on the Indonesia Stock Exchange. These results do not support the signaling theory where the disclosure of financial statements is able to provide a good signal to investors and potential investors. And the results of this study have not been able to support agency theory as a link between managerial ownership and stock returns.